Influência dos atributos do solo nos processos de retenção do herbicida diuron - Chagas, Paulo Sérgio Fernandes (2017)
Weed control efficiency and the environmental fate of herbicides depend on the interactions between the pesticide molecule and the soil. Knowledge of these factors is essential to increase weed control efficiency and reduce environmental contamination of these products. Two experiments were carried out to evaluate the relationship between sorption and desorption of the herbicide diuron and the attributes of different soils. In the first experiment, the multivariate analysis was used to define groups of homogeneous soils and, later, to define the range of sorption and desorption of these soils. In the second experiment, we analyzed the possible influence of pH, by the addition of limestone, on soil retention of the herbicide, sorption and desorption of diuron. The sorption isotherms were evaluated using the herbicide solutions (0.2, 0.4, 0.73, 1.5, 3.0, 6.0 and 12.0 mg L-1) prepared in 10 mmol L-1 CaCl2 and added 10 mL to 2.00 g soil samples for stirring. Desorption was evaluated by the construction of the desorption isotherms from the supernatant collection of the sorption test tubes, to which 10 mL of the 10 mmol L-1 NaCl solution of herbicide was added. All experiments were performed in triplicates using a high performance liquid chromatography system. Soils were grouped according to the similarity of physical-chemical attributes in 4 groups, with G3˃G4˃G2˃G1 being the decreasing order of mean sorption values between groups. This sorption sequence coincides with that of organic matter, which is the main soil component responsible for diuron retention. The desorption sequence was contrary to sorption, due to the reduction of the organic matter. The increase of soil alkalinity increased the sorption of diuron, even reducing part of the organic matter. This increase in sorption occurred by the release of adsorption sites in the colloids or by precipitation of the diuron with Ca+2 or Mg+2. It is concluded that organic matter is the main attribute of the soil that influences the retention processes of diuron in the soil and that the increase of soil pH with the use of limestone increased the sorption due to the occurrence of precipitation of Ca+2 ions and Mg+2 with the herbicide